Molecular characterization of the fibrinogen-erythrocyte interaction and its influence on cardiovascular pathologies by AFM-based force spectroscopy - Malho, Maria Inês de Jesus Freire (2014)
Dissertação para obtenção do Grau de Mestre em Engenharia Biomédica